Obesity and Hormonal Contraception: Safety and Efficacy - Edelman, Alison B.; Jensen, Jeffrey T. (Seminars in Reproductive Medicine, 2012)
The biological capacity for pregnancy complicates the impact of obesity on the health and well-being of women. Consequently, the ability to prevent or plan pregnancies through the use of contraception is critical for obese women. Unfortunately, contraception is often forgotten or feared in women with chronic medical problems like obesity. This review addresses the safety and efficacy of hormonal contraceptive methods in obese women. Generally, the risks of pregnancy outweigh the risks of hormonal contraception in an obese woman, but obesity is a significant risk factor for thrombosis, which should be taken into account when recommending a combined hormonal method. Limited data suggest that the efficacy of some hormonal methods may be reduced in obese women.
Keywords: obesity; body mass index; efficacy; safety; unplanned pregnancy; venous thromboembolism